The Relationship of Nutritional Status with Cholesterol Levels in Junior High School Students in Malang - Monikasari, Monikasari; Nugroho, Kristiawan Prasetyo Agung; Natawirarindy, Chaterine; Esperansa, Priskila Eka Setia (GLOBAL HEALTH SCIENCE GROUP, 2024)
Overweight and obesity are the result of excess food intake compared to energy expenditure. Overweight and obesity are health problems associated with dyslipidemia and risk factors for cardiovascular disease. Knowledge about being overweight and knowledge about nutrition are related to the practice of choosing the food consumed. The aim of this research was to determine the relationship between nutritional status and cholesterol levels in junor hidgh school students in Malang. The method used in this research uses a quantitative descriptive research design with a cross sectional approach. The research location was carried out at Pelita Kasih Lawang Christian Middle School, Malang Regency in February - April 2021. The method used in this research was the total population, with the population in this study being 76 respondents. Respondent characteristics data was obtained based on the population at Pelita Kasih Lawang Christian Middle School, Malang Regency, aged 12-15 years who had more nutritional status and were willing to be respondents when the research was conducted. Nutritional status data was obtained using a weight measuring device using a Camry brand digital scale. Height measuring tool using a micrometer with an accuracy of 0.1 cm. Cholesterol test tool with Easy Touch brand cholesterol strips, non-powdered rubber gloves, 5L biohazard safety box, lancet needle and alcohol swabs. Conclusion: based on the research that has been conducted, it can be concluded that the nutritional status is normal for 36 respondents, the nutritional status is overweight for 11 respondents and the nutritional status for obesity is 7 respondents. There was no relationship between nutritional status and respondents' cholesterol levels. Suggestion: This research still requires further research related to nutritional status and hypercholesterolemia factors.